(untitled) (Research, Society and Development, 2021)
Introduction: Polycystic Ovary Syndrome (PCOS) is one of the most common endocrinopathies in fertile women. It is called hyperandrogenism, which can lead to symptoms such as acne, menstrual irregularities, obesity, ovarian cysts, hirsutism. This can trigger many complications such as infertility and neoplasms, so it is necessary to make an early diagnosis. Exposure to large amounts of intrauterine androgens can lead to the accumulation of fat mass. Objective: To demonstrate the pathophysiological link between obesity and PCOS. Methodology: This is a literature review. The research was conducted through online access in the National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (Scielo), Google Scholar, Virtual Health Library (VHL) and EBSCO Information Services databases, in July 2021 Results and discussion: Adipose tissue has a vast diversity of interactions and cell types, in addition to being metabolically active. In PCOS, obesity is predominantly qualified by an extension in the fat cell size (hypertrophic obesity) more than the extension in the number of adipocytes (hyperplastic obesity). It is likely that the loss of lipolytic function of the adipose tissue is secondary to hyperandrogenism in PCOS patients, which would cause greater insulin resistance. Conclusion: PCOS has a high incidence and if obesity has already assumed epidemic proportions, it is essential to make individuals aware of this reality. Overweight, obesity and, particularly, central obesity can exacerbate it, with possible consequences on the phenotype of the disorder, as well as corroborating problems related to this pathology, such as insulin resistance and cardiovascular problems.